Kesesuaian Strategi Pembelajaran Buku Guru Dan Buku Siswa IPA Terpadu Kelas VII Semester 2 Dalam Kurikulum 2013 - Priharani, Navia, Dr. Siti Chalimah, M.Pd (2015)
Curriculum implementation in 2013 is a learning step that is designed to develop the potential of learners, the generation of the Indonesian with dignity, civilized, cultured, character, and faith, to produce a quality education quality. The existence of in handbooks students IPA of integrated Classes VII semester 2 of government output, as preparation of new curriculum is in education in Indonesia. Research carried out aiming to obtain data regarding the suitability of materials textbooks integrated classes VII of in Curriculum Implementation in 2013. The strategies used is the strategies instrument checklist. This research is a qualitative descriptive study using the technical analysis of the content, which is a research technique that has analyzed the data based on the classification, identification, interpret and infer from the file in the form of a detailed descriptive sentences and candid. The results of the analysis has been carried obtained suitability level learning strategies and student teacher book chapter VI of the number of items 8 of 61.5% or better category, chapter VII of the number of items 9 or 81.8% very good category, chapter VIII with a number item 8 or 66.7% good category, and chapter IX with the number of items 12 or 66.7% good category. Gained an average of 9.25 or by 55.34% fall into either category. The conclusions of this study is the suitability of the learning strategy books science teacher and student book VII semester of second-class integrated into the curriculum implementation in 2013 have both criteria.